Tailoring immunisation programmes: Using behavioural insights to identify barriers and enablers to childhood immunisations in a Jewish community in London, UK. Issue 31 (25th July 2018) - Letley, Louise; Rew, Vanessa; Ahmed, Rehana; Habersaat, Katrine Bach; Paterson, Pauline; Chantler, Tracey; Saavedra-Campos, Maria; Butler, Robb
Highlights: Uncovering barriers and enablers to vaccination among a Charedi Jewish community. The WHO Tailoring Immunization Programmes (TIP) approach was applied. Results showed no indication that a cultural or religious anti-vaccination sentiment existed. Critical issues related to access to and convenience of immunisation services. Behavioural analysis identified subgroups for tailored approaches to meeting parents' needs. Abstract: Introduction: Due to regular vaccine preventable disease outbreaks and sub-optimal immunisation uptake in the London borough of Hackney, home to the largest Charedi Orthodox Jewish community in Europe, it was decided, in consultation with the community, to implement the WHO Tailoring Immunization Programmes approach (TIP). Design: The WHO Tailoring Immunization Programmes (TIP) approach was used. TIP provides a framework based on behavioural insights methodology to identify populations susceptible to vaccine preventable diseases, diagnose supply and demand side barriers and enablers to vaccination and recommend evidence-informed responses to improve vaccination coverage. Results: The results of the formative research and behavioural analysis challenged the assumption that a cultural or religious anti-vaccination sentiment existed within the community. Critical issues related to access to and convenience of immunisation services. Service providers in the area have challenges due to having to deliver immunisation services to the large numbers of children without additional resource. Where mothers were choosing to delay or refuse vaccinations their reasons were broadly similar to the wider population. The behavioural analysis identified potential categorisation of subgroups within the community enabling a more tailored approach to addressing concerns and meeting parents' needs. Conclusion: The TIP approach was an effective way of investigating factors linked to sub-optimal immunisation within the Charedi community. The use of behavioural insights enabled the categorisation of subgroups so that more targeted interventions could be developed. The comprehensive stakeholder engagement which is a key pillar of the TIP approach ensured a deeper understanding of the barriers and enablers to vaccination as well as increasing the level of ownership in the community. TIP should be considered as a useful approach to identify main facilitators and barriers to vaccination in communities with suboptimal immunisation uptake.